2016
DOI: 10.1021/jacs.6b00762
|View full text |Cite
|
Sign up to set email alerts
|

Probing Edge Site Reactivity of Oxidic Cobalt Water Oxidation Catalysts

Abstract: Differential electrochemical mass spectrometry (DEMS) analysis of the oxygen isotopologues produced by (18)O-labeled Co-OEC in H2(16)O reveals that water splitting catalysis proceeds by a mechanism that involves direct coupling between oxygens bound to dicobalt edge sites of Co-OEC. The edge site chemistry of Co-OEC has been probed by using a dinuclear cobalt complex. (17)O NMR spectroscopy shows that ligand exchange of OH/OH2 at Co(III) edge sites is slow, which is also confirmed by DEMS experiments of Co-OEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

27
209
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 210 publications
(239 citation statements)
references
References 46 publications
27
209
0
3
Order By: Relevance
“…In this regard, insights into the details of the OER mechanism in Co-OECs have been greatly aided by molecular model complexes. Complementary electrochemical studies of binuclear cobalt complexes and Co-OECs are consistent with the contention that OER occurs at a dicobalt edge site (23,(25)(26)(27). As illustrated in Fig.…”
supporting
confidence: 83%
See 2 more Smart Citations
“…In this regard, insights into the details of the OER mechanism in Co-OECs have been greatly aided by molecular model complexes. Complementary electrochemical studies of binuclear cobalt complexes and Co-OECs are consistent with the contention that OER occurs at a dicobalt edge site (23,(25)(26)(27). As illustrated in Fig.…”
supporting
confidence: 83%
“…Such exchange coupling provides a mechanism for charge localization within cubanes, as shown here, and by analogy within the metalate clusters of Co-OEC. Isotope labeling studies of oxidic cobalt OER catalysts (23,24) and computational mechanistic studies of Co-OECs (42,43), together with model studies of dicobalt complexes (23), indicate that O-O bond formation requires an adjacent Co(IV) 2 active edge site; it is necessary that two Co(IV) centers localize to the edge site of a cobaltate cluster preceding turnover, as opposed to hole equivalents delocalized over the cluster active site. As we show here, antiferromagnetic coupling provides a mechanism to drive hole localization within the cluster core.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transport of the Co 4+ in CoP i films (i.e., the oxidizing hole equivalent) is predicted to be fast based on the Co 3+/4+ selfexchange electron transfer rate constant of k ET (Co 3+/4+ ) = 3 × 10 5 M -1 ·s -1 measured in cobalt cubane model complexes (31). Delivery of the hole equivalent to the surface of the catalyst allows Co 4+ in CoP i to react with Co 2+ in solution to yield Co 3+ , which adds to edges exposed from dissociation of P i from the cobalt cluster, as observed in substitution kinetics studies of native CoP i (26) and Co 7 metallate clusters (32). These results account for the first order in [Co 2+ ] and inverse order in [P i ].…”
Section: Significancementioning
confidence: 90%
“…Isotopic oxygen labeling studies have shown that OER occurs at edge sites of the cobaltate clusters, with a dicobalt active site as the minimal structural unit that supports catalysis ( Fig. 3) (26). OER catalysis proceeds from a Co(III) "Co(IV)" precatalyst (P) state, as shown by X-ray absorption spectroscopy (XAS) (22,27) and…”
mentioning
confidence: 97%